2011
DOI: 10.1016/j.brainres.2010.09.101
|View full text |Cite
|
Sign up to set email alerts
|

Brain growth across the life span in autism: Age-specific changes in anatomical pathology

Abstract: Autism is marked by overgrowth of the brain at the earliest ages but not at older ages when decreases in structural volumes and neuron numbers are observed instead. This has lead to the theory of age-specific anatomic abnormalities in autism. Here we report age-related changes in brain size in autistic and typical subjects from 12 months to 50 years of age based on analyses of 586 longitudinal and cross-sectional MRI scans. This dataset is several times larger than the largest autism study to date. Results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
470
3
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(522 citation statements)
references
References 66 publications
42
470
3
7
Order By: Relevance
“…Across these studies, grey matter volumes within frontal and temporal lobes were significantly increased in children and adolescents with ASD compared to typically developing individuals (Bloss & Courchesne, 2007;Carper, Moses, Tigue, & Courchesne, 2002;Courchesne, Campbell, & Solso, 2011;Hazlett, Poe, Gerig, Smith, & Piven, 2006;Kates et al, 2004;Palmen et al, 2005;Schumann et al, 2010). However, volumetric measurements of lobular regions do not provide spatially localized information on grey matter abnormalities.…”
Section: Introductionmentioning
confidence: 97%
“…Across these studies, grey matter volumes within frontal and temporal lobes were significantly increased in children and adolescents with ASD compared to typically developing individuals (Bloss & Courchesne, 2007;Carper, Moses, Tigue, & Courchesne, 2002;Courchesne, Campbell, & Solso, 2011;Hazlett, Poe, Gerig, Smith, & Piven, 2006;Kates et al, 2004;Palmen et al, 2005;Schumann et al, 2010). However, volumetric measurements of lobular regions do not provide spatially localized information on grey matter abnormalities.…”
Section: Introductionmentioning
confidence: 97%
“…Epidemiological studies have also demonstrated teratogen exposure during the first trimester to be significantly correlated with an increased risk of developing ASD (Christianson et al, 1994;Rasalam et al, 2005). The developmental emergence of this condition has been associated with abnormal synapse remodelling arising from dysregulation of synaptic development proteins, including cell adhesion molecule function and glycosylation state Pinto et al, 2010;), that inexorably gives rise to an array of neuroanatomical malformations (Courchesne et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Development peaks occur between 2 and 5 years of age, when cranial circumferences are above average and cerebral volume increases, and are followed, in adolescent and adult ages, by reduced cerebral dimension and function (Aylward et al, 2002;Courchesne et al, 2010;Hazlett et al, 2011). The evaluation and monitoring of child development dynamics may be performed using WHO Anthro software (World Health Organization-WHO, 2011), made in accordance with WHO standards (WHO, 2007) for children aged between 0 and 5.…”
Section: Wwwintechopencommentioning
confidence: 99%